Quantitative study of microscopic formation water distribution in tight gas reservoirs based on the thermogravimetric method - Liu, Cheng; Ma, Litao; Liu, Chengzhen; Li, Yangbing; Huang, Ying; Yang, Jianghao; Hu, Weiqiang; Liu, Dengke (Frontiers in Earth Science, 2025)
The microscopic characterization of the distribution of formation water in tight gas reservoirs has always been one of the challenges in the industry. The traditional nuclear magnetic resonance method has certain limitations in characterizing the microscopic distribution of formation water. Thermogravimetric analysis can correlate with mass, and combined with nuclear magnetic resonance spectra, it can further optimize the characterization method for the microscopic distribution of formation water. Multiple tight sandstone gas reservoirs are vertically developed in the Shenfu Block of the Ordos Basin. Due to the strong heterogeneity of the reservoir, given the complexity of the characterization of the microscopic occurrence law of formation water, the typical argillaceous tight sandstone reservoirs Qian 5 and Tai 2 members are selected as the research objects. The distribution characteristics of the microscopic formation water of the tight gas reservoir in the Shenfu block were quantitatively characterized by the thermogravimetric method using dry distillation experiment, nuclear magnetic resonance experiment, and displacement experiment. The results show that 35°C is the boundary temperature between free water and microporous water. According to the characterization of various types of water occurrence in clay and tight sandstone by thermogravimetric experiment, free water below 35°C, microporous water (including capillary water and adsorbed water on the surface of mineral particles) in the range of 35°C–427°C, and clay-bound water (crystal water, structural water/carboxyl water) above 427°C. The type of water occurrence in tight sandstone is consistent with that of clay minerals, but the amount of water occurrence and water loss rate are different. From the perspective of water occurrence, microporous water is typically the most abundant form, while in terms of water loss rate, free water generally exhibits the highest rate. The full-scale quantitative study of micro-formation water distribution in tight gas reservoirs based on the thermogravimetric method has important guiding significance for solving the accurate characterization of water saturation logging in tight gas reservoirs, and enriches the understanding of the occurrence characteristics and laws of micro-formation water in tight gas reservoirs.